TRAF6 regulates melanoma invasion and metastasis through ubiquitination of Basigin - Luo, Zhongling (Oncotarget, 2016)
TRAF6 plays a crucial role in the regulation of the innate and adaptive immune responses. Although studies have shown that TRAF6 has oncogenic activity, the role of TRAF6 in melanoma is unclear. Here, we report that TRAF6 is overexpressed in primary as well as metastatic melanoma tumors and melanoma cell lines. Knockdown of TRAF6 with shRNA significantly suppressed malignant phenotypes including cell proliferation, anchorage-independent cell growth and metastasis in vitro and in vivo. Notably, we demonstrated that Basigin (BSG)/CD147, a critical molecule for cancer cell invasion and metastasis, is a novel interacting partner of TRAF6. Furthermore, depletion of TRAF6 by shRNA reduced the recruitment of BSG to the plasma membrane and K63-linked ubiquitination, in turn, which impaired BSG-dependent MMP9 induction. Taken together, our findings indicate that TRAF6 is involved in regulating melanoma invasion and metastasis, suggesting that TRAF6 may be a potential target for therapy or chemo-prevention in melanoma.